How do Digital Native Students Responses to Balinese Ethnomathematics Problems? - Payadnya, I Putu Ade Andre; Jayantika, I Gusti Agung Ngurah Trisna (Jurnal Pendidikan Progresif, 2022)
How do Digital Native Students Responses to Balinese Ethnomathematics Problems? Objectives: This study determines digital native students' responses to ethnomathematical problems in Balinese culture. Methods: This study uses descriptive analysis techniques. The subjects were 42 students of class VIII.1 and VIII.5 SMP Widiatmika. Data was collected through questionnaires, tests, and interviews. The student response questionnaire consists of 3 aspects, namely familiar or not familiar, appropriate or not appropriate, and interested or not interested. The responses data the percentage of positive and negative responses is then calculated. Findings: The results showed that only 16.67% of students are familiar with Balinese ethnomathematics problems, 95.24% of students considered that the ethnomathematics was appropriate in learning mathematics, and 90.48% of students are interested in ethnomathematics. Conclusion: It was found that digital native students tend to give a positive response but are unable to understand Balinese ethnomathematics. From these findings, Future learning is expected to become a culture and technology-based learning. Keywords: digital native students, ethnomathematics, student response, problem solving, balinese culture.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202230